The temporal analysis of elite breaststroke swimming during competition - Nicol, E.; Adani, N.; Lin, B.; Tor, E. (Sports Biomechanics, 2021)
Breaststroke is the only competitive stroke characterised by propulsive discontinuity. It is consequently paramount that swimmers optimally coordinate limb movements in order to maintain the highest average velocity possible. The present study aimed to investigate the temporal patterns of elite breaststroke swimmers. 50 m long-course competition footage of (1) 20male 100 m races, (2) 24 female 100 m races, (3) 15 male 200 m races, and (4) 27 female 200 m races from 2018 to 2020 were digitised and analysed. Six points within each stroke cycle were identified and used to calculate 15 temporal parameters. Analyses revealed multiple temporal pattern differences between groups based on sex and race distance. It is recommended that coaches individualise swimmers' breaststroke temporal patterns based on individual needs, strengths, and morphological characteristics.